Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.omtn.2021.06.024
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenomic signature for molecular classification in hepatocellular carcinoma

Abstract: Immunity plays an important role in tumor development. In this study, we aimed to investigate molecular classification and its prognostic value in hepatocellular carcinoma (HCC) based on immune signature. Gene set enrichment analysis (GSEA) was used to calculate scores of immune pathways for HCC and hierarchical clustering in two databases (The Cancer Genome Atlas [TCGA], Liver Cancer-RIKEN, JP [LIRI_JP]). The scores of the immune microenvironment and the proportions of 22 immune cells were also calculated. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 37 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is a heterogeneous type of cancer that varies vastly in clinical outcome and response to therapy. Although several studies have identified important molecular classes in HCC, uncertainty remains regarding their associations with outcomes and their complex interaction with liver regenerative processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recently, our lab defined three distinct molecular-based subpopulations of HCC tumors, namely HCC, Blast-Like, and CCA-like, based on gene expression similarity to cholangiocarcinomas and hepatoblast cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a heterogeneous type of cancer that varies vastly in clinical outcome and response to therapy. Although several studies have identified important molecular classes in HCC, uncertainty remains regarding their associations with outcomes and their complex interaction with liver regenerative processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recently, our lab defined three distinct molecular-based subpopulations of HCC tumors, namely HCC, Blast-Like, and CCA-like, based on gene expression similarity to cholangiocarcinomas and hepatoblast cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, majority of member genes of CLST are closely related to LILs and functional transition of LILs in liver microenvironment. However, these previous studies are performed based on flow cytometry(FCM), immune fluorescence (IF) and immunohistochemistry (IHC) with a limited subpopulations of LILs and samples size (50) (36) (51) (52),the crosstalking between CLST with a variety of LILs/immunogenomic pathways are not comprehensively investigated due to the absence of efficient tools for defining further richness of LILs and immunogenomic pathways from high through transcriptomic data until GSEA based algorithms (31,60) and other algorithms including CIBERSORT(61), MCP-counter, TIMER et al were developed (31,60,62,63).Nowadays, GSEA based algorithms have been widely used in tumor (29,31,(64)(65)(66)(67) and non-tumor researches (32,68,69) for immunogenomic signatures/pathways identification. According to the previous studies (31,32,67,69),we calculated ES of 28 LILs by cell marker gene based ssGSEA algorithm in HBV related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The orchestra of viral factors , parenchymal hepatic cells , tissue-resident lymphocytes and extrahepatic immune cells in liver microenvironment is highly associated with HBV related diseases processes (30).Until now, intrahepatic landscape of immunophenotypes and their diagnosis values remind largely unknown and few studies identified core immune signals during disease progression from initial HBV infection to HBV-HCC by Single-sample gene set enrichment analysis (ssGSEA) widely used in immunogenomic biosignatures identification (3,29,(31)(32)(33). Intrahepatic chemokines play pivotal roles in the initiate recruiting extrahepatic pathogenic T cells (34)(35)(36)(37) (38), ECM deposition are drivers of malignant liver diseases (39,40) , but these genes in liver tissues as a whole and their cross-talking with intrahepatic immune cells across disease stages for candidate biomarkers development,as well as therapeutical targets for immune interruption are still far from being investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease progression is influenced by immune cell infiltrations in the TME. In several cancers, immune-related indicators correlate better with clinical outcomes, relative to TNM staging [18][19][20]. Therefore, immune scores associated with TME are essential components of the staging system [21].…”
Section: Discussionmentioning
confidence: 99%